The Effectiveness of Cloud-Based E-Learning towards Quality of Academic Services: An Omanis’ Expert View - Alajmi, Qasim; Adzhar, Kamaludin; Ruzaini, Abdullah Arshah; Al-Sharafi, Mohammed A. (The Science and Information (SAI) Organization Limited, 2018)
The purpose of this paper is to understand the importance, relevance and the need of implementing Cloud-Based E-Learning (CBEL) in Higher education institutions (HEIs) in Oman. The paper maintains its emphasis on addressing the effectiveness of the cloud based e-learning system and also takes into account the activities of comparing and contrasting the before and after effects of the implementation of the CBEL on higher educational sector in Oman. Method: The methodological approach of this paper follows qualitative approach of data collection and the data analysis techniques used in this paper are interpretivist approach and thematic analysis. Results and Findings: The data analysis techniques used in this research paper helped in understanding and gathering meaningful insights relating to the need and significance of implementing CBEL in educational sectors.